Biocompatibility and Comfort during Extended Wear of Mel4 Peptide-Coated Antimicrobial Contact Lenses - Parthasarathi Kalaiselvan; Debarun Dutta; Nagaraju Konda; Pravin Krishna Vaddavalli; Savitri Sharma; Fiona Stapleton; Mark D. P. Willcox (MDPI AG, 2022)
(1) Purpose: This study aimed to investigate the effects of Mel4 antimicrobial contact lenses (MACL) on the ocular surface and comfort during extended wear. (2) Methods: A prospective, randomised, double-masked, contralateral clinical trial was conducted with 176 subjects to evaluate the biocompatibility of contralateral wear of MACL. The wearing modality was 14-day extended lens wear for three months. The participants were assessed at lens dispensing, after one night, two weeks, one month and three months of extended wear and one month after study completion. (3) Results: There were no significant differences (p > 0.05) in ocular redness or palpebral roughness between Mel4 and control eyes at any of the study visits. There was no significant difference (p > 0.05) in corneal staining between Mel4 and control eyes. There were no significant differences in front surface wettability or deposits or back surface debris (p > 0.05). No statistically significant differences (p > 0.05) were found in comfort, dryness, CLDEQ-8 scores lens or edge awareness. There was no evidence for delayed reactions on the ocular surface after cessation of lens wear. (4) Conclusion: The novel MACLs showed similar comfort to control lenses and were biocompatible during extended wear. Thus, these lenses were compatible with the ocular surface.